A brief overview of Colum Mccann’s works and prose style - Khajieva Feruza; Rakhimova Shakhnoza (International Journal Of Literature And Languages, 2025)
Colum McCann is a renowned Irish writer and the author of Let the Great World Spin, TransAtlantic, and Apeirogon. His works explore important themes such as migration, historical memory, social inequality, and human solidarity. McCann masterfully blends reality and fiction, creating poignant and profound stories that resonate with readers worldwide. This article examines his style, key themes, and influence on contemporary literature.